Rome and religion in the medieval world studies in honor of Thomas F.X. Noble - Garver, Valerie L. 1972-; Phelan, Owen M.; Noble, Thomas F. X. 1947- (Church, faith and culture in the medieval West, 2014)
Thomas F.X. Noble : an appreciation / Valerie L. Garver and Owen Phelan -- Bibliography of the works of Thomas F.X. Noble -- Discipuli nobilis : a listing of the students of Thomas F.X. Noble -- "Whatever mystery may be given to my heart" : a latent image in Arator's History of the apostles / Giselle de Nie -- Getting to know Virgil in the Carolingian age : the Vita publii Virgilii / John Contreni -- Why not to marry a foreign woman : Stephen III's letter to Charlemagne / Walter Pohl -- Opposition to pilgrimage in the reign of Charlemagne? / Janet Nelson -- The sources of textiles and vestments in early medieval Rome / Maureen C. Miller -- Christening, the kingdom of the Carolingians, and European humanity / John Van Engen -- The astronomer's life of Louis the Pious / David Ganz -- Paschasius Radbertus and Pseudo-Isidore / Mayke de Jong -- Care of relics in early medieval Rome / Julia M.H. Smith -- Rome and the popes in the construction of institutional history and identity in the early Middle ages : the case of Leiden Universiteitsbibliotheek Scaliger Ms 49 / Rosamond McKitterick -- What's in a psalm? : British Library Ms. Arundel 60 and the stuff of prayer / Rachel Fulton Brown -- Prolegomenon to a study of the Vienna Coronation Gospels : common knowledge, scholarship, tradition, legend, myth / Lawrence Nees -- Toward evolution : the structure of scientific revolutions and the receptions of the Libri Carolini in the seventeenth century / Karl F. Morrison